2005
DOI: 10.1021/ac048196z
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic Segregation of Different Human Cell Types on Microscope Slides

Abstract: A new method for preparing cells for microscopic examination is presented in which cell mixtures are fractionated by dielectrophoretic forces and simultaneously collected into characteristic zones on slides. The method traps cells directly from the suspending medium onto the slide, reducing cell loss. Furthermore, it exploits differences in the dielectric properties of the cells, which sensitively reflect their morphology. Because different cell types are trapped in characteristic zones on the slide, the techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 26 publications
3
57
0
Order By: Relevance
“…Surprisingly, the platelets suspended in the LEC buffer showed lower levels of CD 62P expression compared to those in Tyrode's buffer suggesting that the use of LEC buffer does not have a detrimental effect on the platelet activation. This finding is consistent with other reports which found that sugar-based buffers have a minimal effect on the viability of other mammalian cell types [35][36][37].…”
Section: Effect Of Lec Buffer On Platelet Activationsupporting
confidence: 93%
“…Surprisingly, the platelets suspended in the LEC buffer showed lower levels of CD 62P expression compared to those in Tyrode's buffer suggesting that the use of LEC buffer does not have a detrimental effect on the platelet activation. This finding is consistent with other reports which found that sugar-based buffers have a minimal effect on the viability of other mammalian cell types [35][36][37].…”
Section: Effect Of Lec Buffer On Platelet Activationsupporting
confidence: 93%
“…Many researchers have reported their findings in the area of blood cell separation [1,2]. However, there remains a great need for novel techniques involving innovative structures that can be used at the point of care, on minimal volumes of blood specimen, with high speed and enhanced accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In contrast, label-free methods typically utilize differences in physical properties such as cell size, 10 density, 11 cell adhesion, [12][13][14][15] and dielectric properties. [16][17][18] One potential drawback in label-free methods is that the physical difference is not high enough for efficient separation in many cases, which limits the widespread use of the label-free methods. Nonetheless, the efficiency of separation could be enhanced under controlled micro/nanoenvironments by amplifying the physical differences.…”
Section: Introductionmentioning
confidence: 99%